2022
DOI: 10.1109/access.2022.3169591
|View full text |Cite
|
Sign up to set email alerts
|

Design and Cascade PI Controller-Based Robust Model Reference Adaptive Control of DC-DC Boost Converter

Abstract: In this paper, Cascade PI Controller-Based Robust Model Reference Adaptive Control (MRAC) of a DC-DC boost converter is presented. Non-minimum phase behaviour of the boost converter due to right half plane zero constitutes a challenge and its non-linear dynamics complicate the control process while operating in continuous conduction mode (CCM). The proposed control scheme efficiently resolved complications and challenges by using features of cascade PI control loop in combination with properties of MRAC. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Figure 13 is a component of the prototype mechanism used for this research, for the experiment to be shown in the following section. Nevertheless, the following sections are simulated using mathematical models of the MATLAB/Simulink program to compare with prototype mechanism experiments produced to control the single-channel DC/DC boost converter circuit with artificial neural networks, fuzzy logic and PID controllers [33].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 13 is a component of the prototype mechanism used for this research, for the experiment to be shown in the following section. Nevertheless, the following sections are simulated using mathematical models of the MATLAB/Simulink program to compare with prototype mechanism experiments produced to control the single-channel DC/DC boost converter circuit with artificial neural networks, fuzzy logic and PID controllers [33].…”
Section: Resultsmentioning
confidence: 99%
“…The conventional boost converter can step the input voltage up to three or four times because the high output voltage demands high duty cycle values; therefore, this is one of the most popular topologies [108,109]. This converter leads the switch to remain on for long time intervals [110]. Boost converters' efficiency can reach above 90% under optimal conditions [111].…”
Section: Ude For Dc-dc Boost Converter For Solar Pv and Bessmentioning
confidence: 99%
“…If these characteristics change, the controller may not perform adequately [49]. One of the limitations of this controller is its inability to respond to external disturbances such as load changes [50].…”
Section: B Control Of Boost Convertersmentioning
confidence: 99%